Utilization of Integrated Child Development Services (ICDS) and its linkages with undernutrition in India - Shri K. Singh; Alka Chauhan; Harold Alderman; Rasmi Avula; Laxmi K. Dwivedi; Rati Kapoor; Trupti Meher; Purnima Menon; Phuong H. Nguyen; Sarang Pedgaonker; Parul Puri; Suman Chakrabarti (Maternal and Child Nutrition, 2024)
Abstract The Integrated Child Development Services (ICDS) programme has been the central focus of the POSHAN Abhiyaan to combat maternal and child malnutrition under the national nutrition mission in India. This paper examined the linkages between utilization of ICDS and underweight among children aged 6–59 months. The study utilized data from two recent rounds of the National Family Health Survey (NFHS‐4 [2015–2016] and NFHS‐5 [2019–2021]). Descriptive analyses were used to assess the change in utilization of ICDS and the prevalence of underweight at the national and state levels. Multivariable logistic regressions were performed to examine factors associated with the utilization of ICDS and underweight. Linkages between utilization of ICDS and underweight were examined using the difference‐in‐differences (DID) approach. Utilization of ICDS increased from 58% in 2015–2016 to 71% in 2019–2021. The prevalence of underweight decreased from 37% to 32% in the same period. Changes in ICDS utilization and underweight prevalence varied considerably across states, socioeconomic and demographic characteristics. Results from decomposition of DID models suggest that improvements in ICDS explained 9%–12% of the observed reduction in underweight children between 2016 and 2021, suggesting that ICDS made a modest but meaningful contribution in addressing undernutrition among children aged 6–59 months in this period.